2021
DOI: 10.1111/cas.15084
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive fusion detection using plasma cell‐free RNA in non‐small‐cell lung cancers

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 39 publications
(81 reference statements)
0
21
0
Order By: Relevance
“…At such low rates, ct DNA detections will need to improve significantly and be specialized to reduce the chance of error. A similar situation is true for cf RNA because blood contains mRNA, miRNA, and RNA fragments, which act as noise and contribute to the false detection of RNA [ 69 ]. In addition, the shorter half-life of ct DNA and cf RNA is another challenge that causes a range of problems, from tracking tumor heterogeneity to precision treatment.…”
Section: Applications Of Cf Dna and Cf ...mentioning
confidence: 99%
See 1 more Smart Citation
“…At such low rates, ct DNA detections will need to improve significantly and be specialized to reduce the chance of error. A similar situation is true for cf RNA because blood contains mRNA, miRNA, and RNA fragments, which act as noise and contribute to the false detection of RNA [ 69 ]. In addition, the shorter half-life of ct DNA and cf RNA is another challenge that causes a range of problems, from tracking tumor heterogeneity to precision treatment.…”
Section: Applications Of Cf Dna and Cf ...mentioning
confidence: 99%
“…The diagnosis of cancer through cf RNA can also be conducted by using a urine analysis; Kim et al reported that the urine of bladder cancer patients has higher levels of cf RNA compared to healthy persons. Multiple studies have shown the effective diagnostic capabilities of cf RNA in different cancer types, including breast cancer [ 67 ], colorectal cancer [ 68 ], lung cancer [ 69 ], and many others.…”
Section: Applications Of Cf Dna and Cf ...mentioning
confidence: 99%
“…However, one of the most relevant issues to address is the assessment of gene fusions in liquid biopsy. Their detection by the NGS-based cfDNA analysis is challenging and the sensitivity of detecting in cfDNA is currently debated [ 66 , 67 ]. Moreover, recent reports describe an incidence of detection of gene fusions in plasma samples lower than expected in NSCLC [ 68 , 69 ].…”
Section: Liquid Biopsy As the Challenge Of Todaymentioning
confidence: 99%
“…In fact, analysis of cfRNA in circulation or embedded in vesicles or tumour-educated platelets (TEPs) has shown widely applicability in the detection of several cancer-associated aberrations [ 73 , 74 ]. The sensitivity of cfRNA-based assays could reach over 77% [ 67 ]; however, its clinical implementation is to be improved and needs standardisation of liquid biopsy workflow and optimisation of pre-analytical conditions.…”
Section: Liquid Biopsy As the Challenge Of Todaymentioning
confidence: 99%
“…In contrast to cfDNA, cfRNA-based assays are not affected by intronic regions and only identify expressed fusion genes [117]. In a recent exploratory study, the authors demonstrated that a cfRNA-based NGS assay has an overall higher sensitivity to detect ALK, ROS1, and RET fusions than a cfDNA-based NGS system (78% and 33%, respectively) [122]. Furthermore, amplicon-based NGS panels that analyze gene fusions at the ctRNA level and gene alterations at the ctDNA level may also hold promise in improving fusion detection [89,123].…”
Section: Technical Limitations Leading To False Positive and Negative...mentioning
confidence: 99%